Penguatan Literasi Keuangan, Digitalisasi Ekonomi, dan Ekonomi Kreatif Melalui Edukasi Rupiah, Sosialisasi Qris, Workshop Striphone, dan Ecoprint di Nagori Marihat Bukit - Nadya Zahwani Saragih; Adinda Afifa; Sandrina Meivi; Egicha Putri Wayuling Dinanti; Muhammad Alfikri (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
This study aims to analyze the implementation of programs strengthening financial literacy, economic digitalization, and the creative economy carried out by students participating in the Community Service Program (Kuliah Kerja Nyata/KKN) in Nagori Marihat Bukit. The programs included education on the Indonesian rupiah and the importance of saving habits, socialization of the QRIS digital payment system, a workshop on striphone production to support MSME development, and an ecoprint workshop for elementary school students. The study employed a qualitative descriptive method, with data collected through participatory observation and documentation. The results indicate that the programs successfully enhanced community understanding of financial literacy from an early age, increased the adoption of digital payment technology with 68% of participants successfully implementing QRIS, and improved creative economy skills that support the development of local MSMEs. These activities demonstrate that community-based economic education can effectively strengthen financial awareness, promote digital financial inclusion, and sustainably develop the creative economic potential of the community. Therefore, this KKN program can serve as a practical model of community-based economic empowerment in fostering economically independent communities.